2013
DOI: 10.4103/0971-4065.109421
|View full text |Cite
|
Sign up to set email alerts
|

Oral and salivary changes among renal patients undergoing hemodialysis: A cross-sectional study

Abstract: We wanted to assess oral and salivary changes in end stage renal disease (ESRD) patients undergoing hemodialysis (HD) and to understand the correlation of such changes with renal insufficiency. The cross-sectional study was performed among 100 ESRD patients undergoing HD. Among these, 25 patients were randomly selected to assess the salivary changes and compared with 25 apparently healthy individuals who formed the control group. Total duration of the study was 15 months. Oral malodor, dry mouth, taste change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 14 publications
7
61
1
9
Order By: Relevance
“…19 Patients with reduced salivary flow usually show associated oral signs and symptoms as a result of the reduced quantity of saliva. 20 In the present study, 80%…”
Section: Discussionmentioning
confidence: 97%
“…19 Patients with reduced salivary flow usually show associated oral signs and symptoms as a result of the reduced quantity of saliva. 20 In the present study, 80%…”
Section: Discussionmentioning
confidence: 97%
“…Other studies reported different prevalence of 91% (Patil et al, 2012) and 12.22% (Oyetola et al, 2015) respectively. It has been suggested that complaint of xerostomia or dry mouth in CKD patients is due to fluid restriction, electrolyte imbalance, the use of certain medications such as frusemide and hydrochlorothiazide (anti-hypertensives), mouth breathing secondary to lung perfusion problems, and possible salivary gland alteration (atrophy of minor salivary glands' parenchyma) which resulted in reduced saliva secretion (Kaushik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the reduced function of kidneys to excrete urea out of the body, hence there is increased concentration of urea in the blood (uraemia) as well as in the saliva. Besides, CKD patients often neglected their oral hygiene (Kaushik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…En los tejidos blandos se puede encontrar: agrandamiento gingival (12)(13)(14)(15), gingivitis (10,16), sangrado gingival (8,17), palidez de la mucosa (7,9), petequias y equimosis (9), lengua saburral (13,18,19), úlceras bucales (6,9,20), candidiasis (17,21,22), queilitis angular (12,23,24). En los tejidos duros se puede observar: placa bacteriana y cálculo dental (17,25,26), caries dental (7), erosión dental (8,10,11), hipoplasia del esmalte (6,11,27), pérdida de inserción y movilidad dental (10,13) y disfunción temporomandibular (21,28).…”
Section: Introduccionunclassified
“…En los tejidos duros se puede observar: placa bacteriana y cálculo dental (17,25,26), caries dental (7), erosión dental (8,10,11), hipoplasia del esmalte (6,11,27), pérdida de inserción y movilidad dental (10,13) y disfunción temporomandibular (21,28). A nivel de glándulas salivales se puede observar: xerostomía (8,17,18), disgeusia (8,9,12) y halitosis (6,9,17).…”
Section: Introduccionunclassified